Place re-making and sense of place after quarrying and social-ecological restoration - Kamila Svobodova; Tobias Plieninger; Petr Sklenicka (Sustainable Development, 2023)
Rapid urbanization increases pressure on extracting construction materials through quarrying, which is disrupting and re-making places worldwide. In this study, we examine how people's place making and sense of place are reconfigured through quarrying. Taking a case study approach, we investigate perceptions of sense of place after quarrying and social-ecological restoration in a limestone region of the Czech Republic. Our survey of 400 visitors shows that quarrying affects sense of place through feelings, activities, and quarry features. These can be predicted by socio-demographic characteristics, experiences and preferences, and the context of a particular quarry. We conclude that sense of place and place making should be key themes of the sustainable development debate, as they help to better understand the human variables that constrain or enable socially just development. Our approach provides a conceptual basis for this by revealing the processes through which people iteratively recreate their connections to places shaped by long-lasting disruptions, such as mining and quarrying, that erased prior socio-cultural and material landscapes.
Keywords: 330; mining; place attachment; place making; social-ecological systems; sustainability; values